El surgimiento de la gestión educativa como campo de estudio en América Latina (The emergence of educational management as a field of study in Latin America) - Oplatka, Izhar (Revista Eletrônica de Educação, 2019)
In this article, the author advocates the creation of a field of study of educational management specifically oriented to Latin American educational contexts and criticizes the blind adoption of imported concepts and foreign theories. Relying on the literature of the sociology of knowledge, research in education and the epistemology of science, he succinctly analyzes the development of educational management as an Anglo-American field of study, then focuses on the main differences between educational systems in the Latin American school leadership and in the Anglo-American nations. In his conclusion, the author suggests four challenges for Latin American scholars and researchers focused on educational management and leadership, among which are the generation of applied knowledge from and for the Latin American educational system and the exploration of new specific areas of study of the Latin American contexts. Resumo Neste artigo, o autor defende a criação de um campo de estudo da gestão educacional voltado especificamente para contextos educativos da América Latina e critica a adoção cega de conceitos importados e teorias estrangeiras. Com base na literatura da sociologia do conhecimento, investigação em educação e epistemologia da ciência, ele sucintamente analisa o desenvolvimento da gestão educacional como um campo de estudo anglo-americano, para em seguida destacar as principais diferenças entre os sistemas de ensino e a liderança escolar latino-americana e as das nações anglo-americanas. Em sua conclusão, o autor sugere quatro desafios para acadêmicos e pesquisadores da América Latina com foco em gestão educacional e liderança, entre os quais a geração de conhecimento aplicado de e para o sistema educacional da América Latina e explorar novas áreas de estudo específicas dos contextos latino-americanos. Resumen En este artículo el autor aboga por la creación de un campo de estudio de la gestión educativa específicamente orientado a los contextos educativos latinoamericanos y critica la adopción ciega de conceptos importados y teorías foráneas. Apoyándose en la literatura de la sociología del conocimiento, de la investigación en educación y de la epistemología de las ciencias, analiza sucintamente el desarrollo de la gestión educativa como campo de estudio anglo-norteamericano, para luego focalizarse en las principales diferencias entre los sistemas educativos y el liderazgo escolar latinoamericanos y en las naciones anglo-norteamericanas. En su conclusión, el autor sugiere cuatro desafíos para los académicos e investigadores latinoamericanos centrados en la gestión educativa y el liderazgo, entre los que destacan la generación de conocimientos aplicados desde y para el sistema educativo latinoamericano y la exploración de nuevas áreas de estudio específicas a los contextos latinoamericanos. Keywords: Educational management, Leadership, Latin America, Anglo-American nations. Palavras-chave: Gestão educacional, Liderança, América Latina, Nações anglo-americanas. Palabras claves: Gestión educativa, Liderazgo, América Latina, Las naciones anglo-americanas. References ANDERSEN, M.E. Peoples of the earth: Ethno-nationalism, democracy, and the indigenous challenge in "Latin" America. Plymouth: Lexington Books, 2010. ANDERSON, J.B. Principals' role and public primary schools' effectiveness in four Latin American cities. Elementary School Journal, 109(1), 2008, pp. 36-60. BASSEY M. Case study research in educational settings. Buckingham: Open University Press, 1999. BLACKMORE, H. The modern world: Latin America. Oxford: Oxford University Press, 1966. BOYER, E.L. Scholarship reconsidered: Priorities of the professoriate. Princeton, N.J.: The Carnegie Foundation for the Advancement of Teaching, 1982. BRIDGES, D. The disciplines and discipline of educational research. Journal of Philosophy of Education, 40(2), 2006, pp. 259-272 BUSH, T.; MOLOI, K. Race and racism in leadership development. In: J. LUMBY; G. CROW; P. PASHIADRIS (eds.), International handbook on the preparation and development of school leadership. Nueva York: Routledge, 2008, pp. 104-118. CALLAHAN, R.E. Education and the Cult of Efficiency, The University of Chicago Press, Chicago, 1962. CAMPBELL, R.F. The professorship in educational administration: A personal view. Educational Administration Quarterly, 17(1), 1981, pp. 1-24. CHAPMAN, D.W. Trends in educational administration in developing Asia, Educational Administration Quarterly, 36(2), 2000, pp. 283-308. CULBERTSON, J.A. Trends in educational administration in the United States. Educational Management & Administration, 2(2), 1974, pp. 1-8. CULBERTSON, J.A. A century's quest for a knowledge base. In: BOYAN, N.J. (eds.), Handbook of research on educational administration. Longman, Nueva York, 1988, pp. 3-26. DIMMOCK, C; WALKER, A. Comparative educational administration: Developing a cross-cultural conceptual framework. Educational Administration Quarterly, 34 (4), 1998, pp. 558-595. ESCOBAR, A. Latin America at a crossroads: Alternative modernizations, post-liberalism, or post-development? Cultural Studies, 24(1), 2010, pp. 1-65. EVERTON, T.; GALTON, M.; PELL, T. Educational research and the teacher. Research Papers in Education, 17(4), 2002, pp. 373-401. FOSTER, W. Administrative science: The postmodern and community. In: P.T. BEGLEY (ed.), Values and educational leadership. Nueva York: State University of New York Press, 1999, pp. 97-113. GARCÍA-GARDUNO, J.M.; SLATER, C.L.; GOROSAVE, G.L. Issues in educational administration in Mexico. In: A.W. WISEMAN (ed.), Educational leadership: Global contexts and international comparisons. Bingley: Emerald, 2009, pp. 377-398 GIBBONS, M.; LIMOGES, C.; NOWOTNY, H.; SCHWARTZMAN, S.; SCOTT, P.; TROW, M. The new production of knowledge. Londres: Sage, 1994. GRIFFITHS, D.E. Evolution in research and theory: A study of prominent researchers. Educational Administration Quarterly, 19(3), 1983, pp. 201-221. GWYNNE, R.N.; KAY, C. Latin America transformed: Globalization and Neoliberalism. In: R.N. GWYNNE; C. KAY (eds.), Latin America transformed: Globalization and modernity. Nueva York: Routledge, 2004, pp. 3-21. HALLINGER, P. A conceptual framework for systematic reviews of research in educational leadership and management. Journal of Educational Administration, 51(2), 2013, pp. 126-149. HALLINGER, P. Educational change in East Asia. Journal of Educational Administration, 36(5), 1998, pp. 492-509. HODGKINSON, C. Towards a philosophy of administration. Oxford: Basil Blackwell, 1978. HUMES, W.; BRYCE, T. Scholarship, research and the evidential basis of policy development in education. British Journal of Educational Studies, 49(3), 2001, pp. 329-352. JAQUETTE, J.S. The women's movement in Latin America: Feminist and the transition to democracy. Boulder: Westview Press, 1991. MARIANO, S.R.H.; COSTA E SILVA, F.; MORAES, J. Brazil: Leadership in Brazil. In: H. ARLESTIG, C. DAY & O. JOHANSSON (eds.), A decade of research on school principals: Cases from 24 countries. Heidelberg: Springer, 2015, pp. 445-470. MCCULLOCH, G. Disciplines contributing to education? Educational studies and the disciplines. British Journal of Educational Studies, 50(1), 2002, pp. 100-119. MEYER, P.J. Chile: Political and economic conditions and US relations. In: E.M. BERGER (ed.), Latin and Central America: Economic, Political and social issue. Hauppauge, Nueva York: Nova Science Publisher, 2011. OGAWA, R.T.; GOLDRING, E.B.; CONLEY, S. Organizing the field to improve research on educational administration. Educational Administration Quarterly, 36(3), 2000, pp. 340-357. OPLATKA, I. The principalship in developing countries: context, characteristics and reality. Comparative Education, 40(3), 2004, pp. 427-448. OPLATKA, I. Women in educational administration within developing countries: Towards a new international research agenda. Journal of Educational Administration, 44(6), 2006, pp. 604-624. OPLATKA, I. The field of educational administration: An historical overview of scholarly attempts to recognize epistemological identities, meanings and boundaries from 1960s onwards. Journal of Educational Administration, 2009. OPLATKA, I. The legacy of educational administration: A historical analysis of an academic field. Hamburgo: Peter Lang Publisher, 2010. PASHIARDIS, P.; HEYSTEK, J. School improvement – it is achievable. The enterprise of Education, 2007, pp. 41-60. RIBBINS, P. Leadership and management in education: what's in a field? Latin American Journal of Education, 27(3), 2007, pp. 351-376. RIFFEL, J.A. The study of educational administration: A developmental point of view, Journal of Educational Administration, 24(2), 1986, pp. 152-172. RYNES, S.L.; BARTUNEK, J.M.; DAFT, R.L. Across the great divide: Knowledge creation and transfer between practitioners and academics. Academy of Management Journal, 44(2), 2001, pp. 340-355. SQUIRES, G. Management as professional discipline. Journal of Management Studies, 38(4), 2001, pp. 473-484. TORRES-ARCADIA, C.; RUIZ-CANTISANI, I.; GARCIA-GARDUNO, J.M. Mexico: Research on principals of public schools in Mexico. In: H. ARLESTIG, C. DAY & O. JOHANSSON (eds.), A decade of research on school principals: Cases from 24 countries. Heidelberg: Springer, 2015, pp. 483-502. WALKER, W.G. Administrative narcissism and the tyranny of isolation: Its decline and fall, 1954-1984. Educational Administration Quarterly, 20(4), 1984, pp. 6-23. WEINSTEIN, J.; HERNÁNDEZ, M. Birth pains: emerging school leadership policies in eight school systems of Latin America. International Journal of Leadership in Education, 19(3), 2016, pp. 241-263. WEINSTEIN, J.; MUÑOZ, G. When duties are not enough: principal leadership and public or private school management in Chile. School Effectiveness and School Improvement, vol. 25, issue 4, 2013, pp. 651-670. WHITLEY, R. The intellectual and social organization of the sciences. Oxford: Clarendon Press, 1984. YASHAR, D.J. Contesting citizenship in Latin America: The rise of indigenous movements and the postliberal challenge. Cambridge: Cambridge University Press, 2005.